2015
DOI: 10.1016/j.schres.2014.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Cingulum bundle integrity associated with delusions of control in schizophrenia: Preliminary evidence from diffusion-tensor tractography

Abstract: Background Delusions of control are among the most distinctive and characteristic symptoms of schizophrenia. Several theories have been proposed that implicate aberrant communication between spatially disparate brain regions in the etiology of this symptom. Given that white matter fasciculi represent the anatomical infrastructure for long-distance communication in the brain, the present study investigated whether delusions of control were associated with structural abnormalities in four major white matter fasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
2
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
2
13
2
1
Order By: Relevance
“…That is, schizophrenia patients with severe delusions had nearly normal gray and white matter integrity. Although our findings are in line with several previous studies that reported a positive correlation between structural integrity and delusions in schizophrenia 11 12 13 14 15 16 17 18 19 20 , these findings are inconsistent with other studies that reported a negative correlation between them 21 22 23 24 25 26 27 28 29 30 31 32 33 . The discrepancy across studies may be related to inter-research differences in multiple aspects, such as patient characteristics (subtypes, illness durations, treatments), sample sizes (15–88 cases), imaging techniques (DTI, DKI, diffusion spectrum imaging, and structural MRI), MRI indices (total volume, GMV, white matter volume, gray matter density, white matter density, surface deformity, FA, generalized FA, mean diffusivity, axial diffusivity, radial diffusivity, and probability indices forming part of a bundle of interest), and analytical methods (voxel-wise or ROI-wise analysis, correlation or intergroup comparison).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…That is, schizophrenia patients with severe delusions had nearly normal gray and white matter integrity. Although our findings are in line with several previous studies that reported a positive correlation between structural integrity and delusions in schizophrenia 11 12 13 14 15 16 17 18 19 20 , these findings are inconsistent with other studies that reported a negative correlation between them 21 22 23 24 25 26 27 28 29 30 31 32 33 . The discrepancy across studies may be related to inter-research differences in multiple aspects, such as patient characteristics (subtypes, illness durations, treatments), sample sizes (15–88 cases), imaging techniques (DTI, DKI, diffusion spectrum imaging, and structural MRI), MRI indices (total volume, GMV, white matter volume, gray matter density, white matter density, surface deformity, FA, generalized FA, mean diffusivity, axial diffusivity, radial diffusivity, and probability indices forming part of a bundle of interest), and analytical methods (voxel-wise or ROI-wise analysis, correlation or intergroup comparison).…”
Section: Discussioncontrasting
confidence: 69%
“…To identify neural substrates of delusions, multiple diffusion tensor imaging (DTI) and structural magnetic resonance imaging (MRI) studies have attempted to identify correlations between structural impairments and delusions in schizophrenia ( Supplementary Table S1 and S2 ). However, both positive 11 12 13 14 15 16 17 18 19 20 and negative 21 22 23 24 25 26 27 28 29 30 31 32 33 correlations have been reported. As a measure of cerebral perfusion, both positive and negative correlations between regional cerebral blood flow (CBF) and delusions have been found in schizophrenia 34 .…”
mentioning
confidence: 99%
“…In addition, recent studies found associations of hallucination and delusion severity with WM microstructure in the right inferior longitudinal fasciculus and the connection between the right posterior middle orbitofrontal cortex and the rostral part of the anterior cingulate cortex ( Ohtani et al, 2015 , Seitz et al, 2016 ). Only for delusions researchers found associations with WM properties in the cingulum bundle ( Whitford et al, 2015 ), fornix and external capsule ( Arnedo et al, 2015 ). Moreover, changes in WM microstructure of the left longitudinal fasciculus have recently been shown to correlate with improvements of positive symptoms ( Zeng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2011 , 2012 ; Nortje et al. , 2013 ; Douet and Chang, 2014 ; Ameis and Catani, 2015 ; Whitford et al. , 2015 ).…”
Section: Introductionunclassified